Vertical stabilization of tokamak plasmas via extremum seeking. (September 2022) - Dubbioso, S.; di Grazia, L.E.; De Tommasi, G.; Mattei, M.; Mele, A.; Pironti, A.
Abstract: In this paper we propose a vertical stabilization (VS) control system for tokamak plasmas based on the extremum seeking (ES) algorithm. The gist of the proposed strategy is to inject an oscillating term in the control action and exploit a modified ES algorithm in order to bring to zero the average motion of the plasma along the unstable mode. In this way, the stabilization of the unstable vertical dynamic of the plasma is achieved. The approach is validated by means of both linear and nonlinear simulations of the overall ITER tokamak magnetic control system, with the aim of demonstrating robust operation throughout the flat-top phase of a discharge and the capability of reacting to a variety of disturbances.